The elements of strategic and marketing planning applied in the case of Avital company - Milikic, Sanja (Applied Studies in Agribusiness and Commerce, 2009)
Presently, the environment that is characterized by rapid changesinallsocialspheres,thechallengesofrapidadaptation and survival in the market, the ability of thinking and acting in front of ‘’time’’is one of the key factors of success. Every day we have witnessed a large decline of the number of companies, poor implementation of many projects, poor implementation of governmentreforms, and life challenges of people to find work. On the other hand, there are individuals, organizations and companies that face challenges and changes very fast in all world markets and societies. Question that could be asked based on this is ‘’Why and how some companies manage it and the other not?"